Wetting Behavior of Chitosan Solutions on Blueberry Epicarp with or Without Epicuticular Waxes - Osorio-Lira, F (Springer, 2015)
Edible coatings can prevent microbial spoilage and quality loss of blueberries due to mass transfer (e.g., moisture, gases, aroma compounds, etc.). The protection of blueberry (and in foods in general) by edible coatings depends on controlling the wetting of the coating solutions, which affects the adhesion and the thickness of the film (Park 2002). Indeed, the thickness of edible coatings is an important parameter since it directly affects the biological properties and the shelf-life of blueberries. The central parameter that characterizes the wetting of a blueberry epicarp is the equilibrium contact angle (CA) (Israelachvili 1992). By convention, the CA is the angle, θ, at which a liquid–vapor interface meets the solid surface. Surface free energy (SFE) of blueberry epicarp can be obtained using different approaches. All of these methods are based on CA measurements of different sessile liquid drops with known surface tension deposited on the blueberry epicarp, but discrepancies have been shown in the obtained results (Etzler 2006). One of the main methods for the determination of SFE is the “acid–base” theory of van Oss, Chaudhury, and Good (vOCG) (van Oss et al. 1986, 1988). © 2015, Springer Science+Business Media New York.